Design of multiphase reactors - Pangarkar, Vishwas G. (Hoboken : Wiley, 2015)
'This resource offers a primer on simple design methods for multiphase reactors in the chemical process industries, particularly the fine chemicals industry. It provides the process design engineer with simple yet theoretically sound procedures. Different types of multiphase reactors are dealt with on an individual basis. The book focuses on the problem of predicting mass transfer rates in these reactors. It also contains finally worked examples that clearly illustrate how a highly complex MPR like the Stirred Tank Reactor (STR) can be designed using simple correlations which need only a scientific calculator'--
'This book covers simple design methods for multiphase reactors in the chemical process industries. It is aimed at providing the process design engineer with simple yet theoretically sound procedures. It can also be used as a text for a specialized course/elective for senior undergraduate and post graduate courses. Different types of multiphase reactors are dealt with on an individual basis including two widely used and important reactors that have not received adequate attention particularly: the ventury loop reactor and stirred reactor for cell culture technology. For each reactor type the book discusses the basic theory, develops quantitative models for reactor design and operation and comments on the state of knowledge'--
Includes bibliographical references and index.
Keywords: Chemical reactors